Study of use of saphenoperitoneal shunts in intractable ascites - Yadav, Rajeshwar; Verma, Satyajeet; Rai, Sujeet (International Surgery Journal, 2019)
Background: Ascites is a common complication in patients with chronic liver disease. Ascites usually complicates chronic liver disease, and some patients with ascites are refractory to medical treatment. Recently, saphenoperitoneal shunt was described to treat this condition. This procedure avoids the insertion of a foreign expensive shunt into the circulation. Describe the experience with this procedure with some changes in the technique. Methods: A prospective study was performed on 8 patients with intractable ascites admitted to the surgical ward of Maharani Laxmi Bai Medical College during the period from November 1999 to April 2001. Eight patients with chronic liver disease and diuretic-resistant ascites underwent this procedure. The patients were classified by severity of liver disease as estimated from serum bilirubin and albumin values. Observations were present in tables, number and percentage using Microsoft excel. Results: Procedure performed in 8 patients and was successful 6 patients. Effective doses of diuretics required were decreased to one eighth of the preoperative dose over a median 3 months post- operative period. No patient with successful shunt needed postoperative paracentesis or re-hospitalization in a median follow-up of 8 month. No other complication was found except ascitic leakage. Conclusions: All patients, who had a successful shunt had symptomatic relief from ascites. Therefore the saphenoperitoneal shunt potentially offers all the benefits of peritoneovenous shunting without the disadvantage of using prosthetic material.